The crown. The complete fourth season [videorecording (DVD)] - Morgan, Peter, 1963- (Sony Pictures Home Entertainment, 2021)
"As the 1970s are drawing to a close, Queen Elizabeth and her family find themselves preoccupied with safeguarding the line of succession by securing an appropriate bride for Prince Charles, who is still unmarried at 30. As the nation begins to feel the impact of divisive policies introduced by Britain's first female Prime Minister, Margaret Thatcher, tensions arise between her and the Queen which only grow worse as Thatcher leads the country into the Falklands War. While Charles' romance with a young Lady Diana Spencer provides a much-needed fairy tale to unite the British people, behind closed doors, the royal family is becoming increasingly divided"--Container.